(untitled) (Scientific journal of the Fergana State University, 2023)
This article emphasizes the close connection between language and consciousness, and speech is an expression of this connection. As the sciences such as neuropsychology, psychotherapy, and neurophysiology are developing in our modern society, it is being confirmed year by year that they are directly related to speech centers in the brain. In this article, an attempt was made to explain the role of psycholinguistics in the formation of neurolinguistics as a science, the different views of scientists who conducted research on this topic, and its place in today’s science.